Evaluation of jackfruit germplasm for yield and yield contributing characters (Bangladesh Journal of Agricultural Research, 2019)
Twenty germplasm of jackfruit grown in the Fruit Research Farm of Horticulture Research Centre (HRC), Bangladesh Agricultural Research Institute (BARI) were evaluated for growth, yield and yield parameter along with qualitative characters from July 2012 to June 2015. All the germplasm varied for most of the parameters evaluated. The tallest plant was recorded in AH Joy-079(6.75m) and shortest plant in AH Joy-075 (3.50 m) among the germplasm. Base girth ranged from 42.50 cm to 80.20 cm in AH Joy-075 and AH Joy-085, respectively. Maximum plant spreading with North-South and East-West canopy (5.50 m and 6.00 m, respectively) was recorded in AH Joy-079 and minimum (3.00 m and 3.50m) in both AH Joy-075 and AH Joy-090 germplasm. The fruit number varied from 02 to 11 among the germplasm. Individual fruit weight ranged from 2.27 kg to 11.33 kg where AH Joy-034 had the lowest and AH Joy-092 noted the highest fruit weight. Maximum bulb (184) was recorded in AH Joy-092 and minimum (45) in AH Joy-085. Maximum TSS (25.0) was recorded in AH Joy-029 and minimum (14.0) in AH Joy-067 and the edible portion was noted the highest in AH Joy-036 (48.60%) where it was lowest in AH Joy-078 (32.10%). Bulb texture was soft to hard. Maximum germplasm were juicy to medium juicy having yellow to light yellowPulp. Therefore, The germplasm AH Joy-089, AH Joy-017 and AH Joy-092 may be selected for higher yielder. The germplasm AH Joy-034,AH Joy-067, AH Joy-078,AH Joy-085 and AH Joy-098 should be selected for family size jackfruit as their individual fruit weight ranges between 2 to 4 kg including yellow bulb colourcontaining good juiciness and soft bulb texture.Bangladesh J. Agril. Res. 44(1): 167-177, March 2019